Integration of Augmented Reality for Digital Library Services: Opportunities, Challenges, and Future Trends - Okwu, Emmanuel; Oladokun, Bolaji; Agboke, Abimbola; Chukwu, Emenike (University of Dar es Salaam Library Journal, 2026)
This study investigates the integration of augmented reality (AR) technology in digital library services, highlighting its benefits, associated challenges, and future trends. The study employed a qualitative research design, utilising a systematic review of literature from 2020 to 2024 sourced from Scopus, Web of Science, and Google Scholar. The selected literature was thematically analysed to identify key findings and trends. The findings reveal that AR enhances user experience and engagement, improves accessibility and inclusivity, and offers innovative ways of presenting digital content. Notable advancements include improved hardware, such as sophisticated smartphones and AR glasses, and software integrations with machine learning and AI, enabling more interactive experiences. However, several challenges impede AR integration, including technical and infrastructural limitations, financial constraints, user acceptance, digital literacy, and privacy and ethical concerns. The study concludes that while AR holds significant potential for transforming digital library services, its successful implementation requires addressing these barriers through affordable technology solutions, comprehensive user training, and robust ethical guidelines. Future trends indicate a focus on personalised user experiences, integration with emerging technologies, expanded accessibility, and collaborative learning environments, underscoring the transformative potential of AR in libraries.